Pengembangan Media Pembelajaran Tas Pintar Pada Konsep Dasar Perkalian di SDN 1 Papayan - Furi Dewi, Meitha; Nurfitriani, Meiliana; Taufik Saleh, Yopa (Universitas Nusantara PGRI Kediri, 2020)
This study aims to develop and produce smart learning media products on the basic concept of multiplication at SDN 1 Papayan. This research development uses the Research and Development (R&D) stages that adapt the 4D model. Data analysis techniques used in this study are qualitative and quantitative data analysis techniques. The technique of collecting data in this study used a questionnaire and preliminary tests. The results showed three steps, namely Determining, Designing, and Developing. Based on the product evaluation by the material expert obtained a score of 4.9 in the excellent category. Assessment of the product by media experts scored 5 in the excellent category. Results The product assessment by the teacher scored 5 in the very good category. Scores by 3 students in limited trials obtained an average score of 5 in the excellent category. Product scores by 25 students in the field trials obtained an average score of 4.83 in the excellent category. Overall based on learning outcomes learning media obtained a score of 4.89 in the category of very good smart learning media worthy of being used in the basic concept material multiplication. Results on the initial test before using learning media get an average score of 7.320 increased after learning the basic concepts of multiplication using smart bag learning media on the final test getting a score of 9.120. The results of this study are in accordance with the expectations that students have been able to understand the basic concepts of multiplication as a repetitive addition, so that the smart bag learning media is effective for use in the basic concepts of multiplication